Ўзини ўзи идoрa қилиш – ижтимoий-пcиxoлoгик фeнoмeн cифaтидa (Journal of Universal Science Research, 2023)
This article covers the socio-psychological phenomenon of self-government, theoretical and practical issues related to the formation, management and improvement of self-government motivation, social psychological characteristics of self-government, education.